2007
DOI: 10.1523/jneurosci.2895-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Congruent Activity during Action and Action Observation in Motor Cortex

Abstract: A variety of studies have shown that motor cortical areas can be activated by observation of familiar actions. Here, we describe singleneuron responses in monkey primary motor (MI) and dorsal premotor (PMd) cortices during passive observation and execution of a familiar task. We show that the spiking modulation, preferred directions, and encoded information of cells in MI and PMd remain consistent during both observation and movement. Furthermore, we find that the presence of a visual target is necessary to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
214
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(245 citation statements)
references
References 27 publications
27
214
2
2
Order By: Relevance
“…We confirm that activity within motorrelated cortical areas arises 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010) and that the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). However, in contrast to recent accounts of human amygdala function in social cue integration (Sander et al, 2007;NЈDiaye et al, 2009;Cristinzio et al, 2010;Sato et al, 2010), we found that emotional content is processed earlier within the amygdala and independently of other cues.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We confirm that activity within motorrelated cortical areas arises 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010) and that the interaction between gaze direction and emotion takes place at ϳ200 -300 ms (Klucharev and Sams, 2004;Rigato et al, 2010). However, in contrast to recent accounts of human amygdala function in social cue integration (Sander et al, 2007;NЈDiaye et al, 2009;Cristinzio et al, 2010;Sato et al, 2010), we found that emotional content is processed earlier within the amygdala and independently of other cues.…”
Section: Discussionsupporting
confidence: 79%
“…It has also been established that, when one observes other people's bodily actions, there is activity in motor-related cortical areas (Grèzes and Decety, 2001;Rizzolatti et al, 2001) and that activity reaches these areas 150 -200 ms after the onset of a perceived action (Nishitani and Hari, 2002;Caetano et al, 2007;Tkach et al, 2007;Catmur et al, 2010). Its activity being modulated by social relevance (Kilner et al, 2006) and by eye contact (Wang et al, 2011), the motor system is thus another good neural candidate for the integration of social cues.…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by a recent study suggesting a prominent role for the motor system in predicting the outcome of observed actions by reading body kinematics (Aglioti, Cesari, Romani, & Urgesi, 2008). Moreover, the hypothesis of a more prominent role of M1 in the process of motor simulation has been suggested before (Alaerts, Heremans, Swinnen, & Wenderoth, 2009;Kilner & Frith, 2007;Lepage, Lortie, & Champoux, 2008;Pineda, 2008) and is in line with the recent discovery of M1 neurons with mirror properties in the monkeys brain (Tkach, Reimer, & Hatsopoulos, 2007).…”
Section: Functional Significance and Potential Mechanisms Underlying supporting
confidence: 71%
“…However, a recent experiment indicated that the predominance of muscle-related encoding over direction-related encoding appeared to be independent of the observer's perspective, even though facilitation was generally stronger for the first person perspective (Alaerts et al, 2009) Our findings also contribute to a broader debate over the role of M1 in the context of movement observation. Recent evidence confirms that M1 neurons exhibit mirror properties during movement observation of a highly over-trained task in monkeys (Tkach et al, 2007). However, this M1 activation might simply be a result of strong projections from monkey area F5 located in the IFG (Dum and Strick, 2005), which was argued to represent the core center of the mirror neuron system (Craighero et al, 2007).…”
Section: Predominance Of Muscle-specific Encodingmentioning
confidence: 96%